Knowledge and Awareness Impact on Adherence to Iron Supplementation: Study in Baron sub-district, Nganjuk Regency - Yuliawati, Riza; Ardi Bastian; Agustin Widyowati (Universitas STRADA Indonesia, 2023)
Background: The initial report by the Baron Public Health Centre shows low adherence to iron supplementation among schoolgirls. Therefore, there is a need to identify the causing factors of low adherence. Purpose: Identify and analyse knowledge and awareness of iron deficiency and its impacts on adherence to iron supplements. Methods: A Cross-sectional study on 376 female students in the Baron subdistrict. Data were collected using a questionnaire instrument, and data were analysed using binary regression logistics. Results: A Cross-sectional study with stratified random sampling on 376 female students in the Baron subdistrict. Data were collected using a questionnaire instrument, and data were analysed using binary regression logistics. The majority of respondents have sufficient knowledge of iron deficiency. However, they have low awareness and adherence to iron supplementation. Knowledge has no impact on adherence (p-value 0.823), whereas awareness (p-value 0.000) has a significant impact on adherence to iron supplementation. Conclusion: Knowledge has no impact on iron deficiency adherence, while awareness of iron deficiency prevention influences has a strong impact on adherence to iron supplementation adherence. Innovative programs are needed to increase not only knowledge but also awareness and adherence to iron supplements.